The Living Camera in the Ritual Landscape: The Teachers of the Tatuutsi Maxakwaxi School, the Wixárika Ancestors, and the Teiwari Negotiate Videography - Lea Kantonen; Pekka Kantonen (Journal of Ethnology and Folkloristics)
In this article, we outline the meanings modern Wixárika institutions, such as the school and the museum, may receive as parts of ritual landscape and how the community-based videos shot in the context of these institutions may increase our understanding of ritual landscapes in general. We discuss how ritual landscape can be researched using community-based documentary video art in a way that takes the ontological conceptions of the human and non-human relations of the community seriously. In this case, we understand community-based video art as artistic research in which the work is produced with the community for the community. The making of art, discussed in this article, is a bodily activity as it includes walking with a camera in the Wixárika ritual landscape, interviewing people for the camera, and documenting the work and rituals of the pupils, teachers, and the mara’akate (shaman-priests) planning the community-based museum.